Measurement properties of the Health of the Nation Outcome Scales (HoNOS) family of measures: protocol for a systematic review. Issue 4 (20th April 2018) - Harris, Meredith G; Sparti, Claudia; Scheurer, Roman; Coombs, Tim; Pirkis, Jane; Ruud, Torleif; Kisely, Steve; Hanssen-Bauer, Ketil; Siqveland, Johan; Burgess, Philip M
Abstract : Introduction: The Health of the Nation Outcome Scales (HoNOS) for adults, and equivalent measures for children and adolescents and older people, are widely used in clinical practice and research contexts to measure mental health and functional outcomes. Additional HoNOS measures have been developed for special populations and applications. Stakeholders require synthesised information about the measurement properties of these measures to assess whether they are fit for use with intended service settings and populations and to establish performance benchmarks. This planned systematic review will critically appraise evidence on the measurement properties of the HoNOS family of measures. Methods and analysis: Journal articles meeting inclusion criteria will be identified via a search of seven electronic databases: MEDLINE via EBSCOhost, PsycINFO via APA PsycNET, Embase via Elsevier, Cumulative Index to Nursing and Allied Health Literature via EBSCOhost, Web of Science via Thomson Reuters, Google Scholar and the Cochrane Library. Variants of 'Health of the Nation Outcome Scales' or 'HoNOS' will be searched as text words. No restrictions will be placed on setting or language of publication. Reference lists of relevant studies and reviews will be scanned for additional eligible studies. Appraisal of reliability, validity, responsiveness and interpretability will be guided by the COnsensus-based Standards for the selection of health Measurement INstruments checklist. Feasibility/utility will be appraised using definitions and criteria derived from previous reviews. For reliability studies, we will also apply the Guidelines for Reporting Reliability and Agreement Studies to assess quality of reporting. Results will be synthesised narratively, separately for each measure, and by subgroup (eg, treatment setting, rater profession/experience or training) where possible. Meta-analyses will be undertaken where data are adequate. Ethics and dissemination: Ethics approval is not required as no primary data will be collected. Outcomes will be disseminated to stakeholders via reports, journal articles and presentations at meetings and conferences. PROSPERO registration number: CRD42017057871 .